Analisis Pengendalian Internal Atas Pengeluaran Kas PT. Swabina Gatra - Prima Rizki Imami; Wijaya, R. Muh Syah Arief Atmaja (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2023)
Cash is an asset that is most easily used by employees who are directly in charge of financial management. This is because cash is easily transferable. This study is intended to analyze and determine the system of internal control over cash disbursements of PT. Swabina Gatra has been running well or not. after the existence of these internal controls. The type of research method used in this research is qualitative research. While the data analysis method used in this study is a descriptive analysis method where the analysis contains the facts of the description which are factual, systematic and accrual by comparing the results of the analysis with several theories regarding controlling cash disbursements. Researchers obtained qualitative data by carrying out observations at the research site and conducting direct interviews with the treasurer of PT. Swabina Gatra. The results of the analysis carried out in this study explain that the internal control over cash disbursements of PT. Swabina Gatra is in accordance with the internal control components according to COSO (Organization of the Treadway Commission) but there are components that must be improved, namely the risk assessment component by carrying out an appropriate risk assessment.